COOL DOWN: BURNOUT EDUCATION FOR STUDENTS BASED ON MOBILE APPLICATIONS THROUGH THE MASLACH APPROACH - Putro, Bayu Anggoro; Anggraini, Lussy; Zhofari, Ahmad; Fathni, Luthfia Nadya; Nisrina, Hana Azkia (Jurnal Education and Development, 2025)
The purpose of this study is to interpret Cool Down as educational media to minimize burnout. The method used is research and development: (a) determining the target problem; (b) collecting data on students as a needs test; (c) detailing application content; (d) application design. The statistical test showed that 80% of students in the educational material aspect questionnaire felt that the burnout material was relevant to their needs, 80% of students in the learning style aspect needed flexible educational media, 86% of students in the media preference aspect felt that they needed interactive burnout education, and 85% of students in the application availability aspect questionnaire felt open to this innovation. The validity test of all questions had a total sig (2-tailed) of less than 0.05. Furthermore, the Pearson correlation coefficient was greater than the r-table for 63 respondents, indicating a valid questionnaire. The reliability test was carried out using Cronbach’s Alpha with 0.686> 0.6, indicating that the needs questionnaire had good reliability. The t-test coefficient on the questionnaire of educational material aspect needs, learning style, preferred media on the availability of total sig applications (2-tailed) is smaller than <0.05, which indicates that there is an influence of independent and dependent variables. The mobile application has insightful features such as mind comics, mind infographics, and peer counseling. The stimulus feature represents the students response to burnout material presented through assessments and interactive games. Both features refer to Maslach’s theory that burnout is related to emotional exhaustion, depersonalization, and personal accomplishment.